FRAILTY TRAJECTORIES AMONG WORLD TRADE CENTER GENERAL RESPONDERS. (20th December 2022) - Ko, Fred; Ornstein, Katherine; Pedretti, Nicolo Foppa; Colichino, Elena; Bello, Ghalib; Hung, William
Abstract: As the WTC cohort ages, it is important to examine whether there are differences in frailty trajectories over time in the cohort and examine clinical risk profiles of subpopulations with different trajectories. We used longitudinal data collected annually from the WTC data center and included all individuals with 3+ Clinical Frailty Index (FI) measurements after 9/11 to examine frailty trajectories using latent class growth mixture models. These patterns of change of Clinical-FI all showed an increasing trend over time, but there were three distinct patterns with different rates of increase. These were associated with distinct profiles of characteristics including sociodemographic, occupational and exposure level. WTC responders with higher age, working in construction, and higher-intermediate WTC level of exposure had higher rate of increase of Clinical-FI over time. While WTC responders with younger age, working in protective environment, and with higher education had lower rate of increase of Clinical-FI over time.